Nurse Manager Span of Control in Hospital Settings: An Integrative Review - Angel Boned-Galán; Nieves López-Ibort; Ana Gascón-Catalán (MDPI AG, 2023)
Background: Nurse managers face great challenges in responding to organizational demands. There exists a general mismatch between managerial span of control and the demands of the job post, which can lead to overburdening and attrition. The aim of this review was to identify the effects of the nurse manager span of control on hospital organizations. Methods: An integrative literature review was carried out on nurse manager span of control using the Medline, Embase and Web of Science databases. Results: 21 articles were included. Our findings indicate that the span of control of nursing managers influences outcomes in inpatients, professionals, nurse managers, and the organization. Conclusions: The span of control of each nurse manager must be assessed and adjusted to each case. An appropriate span of control will lead to improved outcomes for stakeholders and the organization as a whole. Implications for nursing management: Tools must be developed and implemented to measure and evaluate the span of control of nurse managers. This study was not registered.